Toxic tropics : a horror story of environmental injustice - Oublié, Jessica, 1983- (Témoins du monde, 2024)
"An in-depth piece of comics journalism exploring the persistent use of the deadly chemical chlordecone to support the banana crops in Martinique and Guadeloupe"--Back cover.